Non-confessional State and Cooperation. Some notes on article 16.3 of the Spanish Constitution - Alcón Yustas, María Fuencisla (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2018)
The Spanish Constitution of 1978 accepts that religion is or could be part of the life of human beings. Therefore, citizens’ religious concerns should be taken into account by civil authorities. This sensibility towards religious realities coheres with the rest of the Constitution. Religious communities also belong to a plural society and their activities are consistent with the constitutional article 9.2. The rights to benefits in religious matters should be based upon the Cooperation Agreements. Both content and implementation then are submitted to the Constitutional mechanism of control. Public powers are forbidden to interfere, e.g. promoting some religions against others.
Keywords: Spanish Constitution; Confessional; Freedom; Conscience; Religion